2009
DOI: 10.1097/gme.0b013e3181967b5d
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiological study of women with urinary incontinence and risk factors for stress urinary incontinence in China

Abstract: Our findings suggest that the prevalence of UI is high in China, with SUI as the most common subtype. Age, vaginal delivery, and others are risk factors for SUI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
150
3
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(176 citation statements)
references
References 21 publications
15
150
3
8
Order By: Relevance
“…Concerning those who sought medical care because of UI, less than half of the women who participated in the study had not been through any prior consultation for such reason. These findings coincide with other reports in the literature, in which 21.3 to 27% of women visited physicians on account of their UI (5,23,24) . Considering the impact on quality of life that such problem can cause, most women in the present study considered loss of urine as a severe problem or felt very upset because of it, differently from the results reported by Hannestad et al, in which most women with incontinence reported it as a mild problem (18) .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Concerning those who sought medical care because of UI, less than half of the women who participated in the study had not been through any prior consultation for such reason. These findings coincide with other reports in the literature, in which 21.3 to 27% of women visited physicians on account of their UI (5,23,24) . Considering the impact on quality of life that such problem can cause, most women in the present study considered loss of urine as a severe problem or felt very upset because of it, differently from the results reported by Hannestad et al, in which most women with incontinence reported it as a mild problem (18) .…”
Section: Discussionsupporting
confidence: 82%
“…The prevalence of UI in the different studies varies broadly, with reports ranging from 17 to 45% of adult women (4)(5) . One of the hypotheses used to explain the broad variation in these studies would be the type of population studied, the definition of UI used and the patient selection criteria.…”
Section: Introductionmentioning
confidence: 99%
“…The only factor of reproductive life significantly associated with UI was the number of vaginal deliveries, which was also found in a study carried out in China with women 20 years old or older, also associated with SUI (26) . During visits to the studied households, feelings such as shock, shame, and embarrassment were observed in some people over the fact that we were addressing urinary leakage, an issue related to intimacy and aspects of which, sometimes, even the spouse was not aware.…”
Section: Resultsmentioning
confidence: 54%
“…A média de idade das mulheres que procuraram atendimento fisioterapêutico para o tratamento de disfunções do AP, bem como as queixas principais estão de acordo com os tipos de queixas descritos em outros estudos [13][14][15] . Atualmente descreve-se que mulheres com sobrepeso ou obesidade têm um risco maior de desenvolver IU 4,14,16-18 e mulheres obesas apresentam medidas de IU mais severas do que mulheres incontinentes com peso normal 19 .…”
Section: Discussionunclassified
“…26 . Em mulheres chinesas de 20 a 99 anos, circunferência abdominal ≥80 cm foi identificada como um dos fatores de risco para IU 15 . Já em enfermeiras dos Estados Unidos, foi observada uma tendência significante de aumento do risco, severidade e frequência de IU com o aumento do IMC e circunferência da cintura.…”
Section: Discussionunclassified